Creative mathematical mental activity of students while solving problems requiring use of Vieta's formulas II - Chronowski, Antoni (Annales Universitatis Paedagogicae Cracoviensis | Studia ad Didacticam Mathematicae Pertinentia, 2020)
This article is a continuation of the article (Chronowski, Powazka, 2016). In this article the next tasks regarding the use of Vieta’s formulas for third degree polynomials (equations) with real coefficients are considered. The Olympic tasks in this article are an inspiration to pupils for creative mathematical activity. In this text, I limited myself to comments, hints and didactic suggestions regarding directly presented tasks and their solutions. The most of the general didactic considerations included in our article (Chronowski, Powazka, 2016) are also valid in this paper.